Poverty assessment initiatives in selected asean countries / Profesor Dr. Roshima Said ... [et al.] - Said, Roshima; Mohd Sidek, Noor Zahirah; Azlyn, Ahmad Zawawi; Ladisma, Mahadir (Universiti Teknologi MARA, Kedah, 2023)
The paper seeks to assess poverty initiatives from selected ASEAN countries, namely Malaysia, Thailand, the Philippines, and Indonesia. The assessment was based on the government's action to deal with poverty. The measurement of poverty was determined according to each ASEAN countries. The findings indicated that countries' governments have struggled due to various problems; all know that this endeavor is difficult to achieve without the participation of all stakeholders in eliminating poverty. The government must consider all the technical implications of whether such modifications in the definition of poverty are necessary and in line with future development policies. Meanwhile, dynamic economic growth is continuously emerging, and the government is exerting efforts via long-term initiatives to ensure a consistent poverty reduction policy. The implications of these assessment reached in developing a sense of ownership and shared responsibility for the SDGs through four platforms—government and parliament, academia and experts, civil society and the media, and charity and business—is one of the government's strategies for eradicating poverty.